A STUDY OF LEXICAL AND STRUCTURAL DIFFERENCES IN MOBY DICK AND ITS INDONESIAN TRANSLATION - Aprillia Anggraini; Derry Pramudia Suisno; Syafina Annazah; Abdul Syahid (LPPM Universitas PGRI Jombang, 2025)
This study investigates the lexical and structural differences between Herman Melville’s Moby Dick and its Indonesian translation, with a focus on preserving the novel’s symbolic, philosophical, and stylistic complexity. Using a qualitative descriptive approach rooted in translation theory, the study critiques existing strategies such as literal translation, transcreation, adaptation, and omission, and introduces a new model, CLASTIC (Contextual Lexical and Structural Translation with Intercultural Calibration). This model addresses the shortcomings of conventional methods by emphasizing contextual interpretation, semantic layering, structural adaptation, and cultural negotiation. Findings reveal that literal translation often leads to a loss of narrative tone and symbolic depth, while uncalibrated adaptation risks distorting authorial intent. The CLASTIC Model successfully bridges linguistic accuracy and cultural sensitivity, offering a comprehensive and applicable framework for translating literary texts from English into Indonesian. The study concludes that effective literary translation demands both interpretive creativity and intercultural awareness, especially when dealing with canonical works marked by complex symbolism and narrative style.